The Common agricultural policy of the European Community : principles and consequences - Rosenblatt, Julius (Washington, D.C. : International Monetary Fund, 1988)
This paper has two purposes, first is to trace the evolution and major developments of the common agricultural policy of the European community and to asses its effects on the economies of the EC member countries and on the rest of the world.
"November 1988."
Bibliography: p. 67-70.
aia 06/03/2019
Loans
Keywords: Agriculture and state